Deskripsi Kompetensi Pedagogik Guru Dalam Pelaksanaan Pembelajaran Di MTS GUPPI Kecamatan Banjit - Rahman Marlingga; Zulkarnain Zulkarnain; Rahma Kurnia Sri Utami (JPG (Jurnal Penelitian Geografi), 2017)
The purpose of this study to determine the pedagogic competence of teachers in the implementation of learning in MTs Guppi Banjit.The research method used is descriptive method. The population in this research is all teachers of MTs Guppi Banjit (1) pedagogical competence about understanding of the students low quality of competence in support of learning activities,score (48.48%) (2) pedagogic competence about curriculum development or syllabus is good enough,score (60.60%),(3) pedagogic competence about the plan of learning design enough,score (60.60%),(4) teacher peagogic competence about communication effectively and impatik quite good (51.51%) teachers MTs Guppi has empathic and high impatient communication seen from the percentage classification 50%, (5) teacher pedagogic competence about the use of learning technology is good enough ,score (63,63%) MTs Guppi high pedagogic competence is seen from the percentage classification 50%.Tujuan penelitian ini untuk mengetahui kompetensi pedagogik guru dalam pelaksanaan pembelajaran di MTs Guppi Kecamatan Banjit.Metode penelitian yang digunakan adalah metode deskriptif.Populasi dalam penelitian ini adalah seluruh Guru MTs Guppi Kecamatan Banjit (1) Kompetensi pedaggogik tentang pemahaman terhadap peserta didik rendah kualitas kompetensi dalam mendukung kegiatan pembelajaran,skor (48,48%),(2) kompetensi pedagogik tentang pengembangan kurikulum atau silabus cukup baik,score (60,60%),(3)kompetensi pedagogik tentang rencana perancangan pembelajaran cukup baik,score (60,60%),(4) kompetensi peagogik guru tentang komunikasi secara efektif dan impatik cukup baik,score (51,51%),(5) kompetensi pedagogik guru tentang pemanfaatan teknologi pembelajaran cukup baik,score (63,63%) guru MTs Guppi kompetensi pedagogik yang tinggi dilihat dari klasifikasi persentasi 50%.Kata kunci: kompetensi,pedagogik,pembelajaran guru